2022
DOI: 10.5194/hess-26-1579-2022
|View full text |Cite
|
Sign up to set email alerts
|

Towards hybrid modeling of the global hydrological cycle

Abstract: Abstract. State-of-the-art global hydrological models (GHMs) exhibit large uncertainties in hydrological simulations due to the complexity, diversity, and heterogeneity of the land surface and subsurface processes, as well as the scale dependency of these processes and associated parameters. Recent progress in machine learning, fueled by relevant Earth observation data streams, may help overcome these challenges. But machine learning methods are not bound by physical laws, and their interpretability is limited… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 89 publications
2
60
0
Order By: Relevance
“…We remove grid cells that have model performance worse than the mean of training data itself using cross-validation out-of-bag score (OOB R 2 > 0). We note that the rather low threshold (OOB R 2 > 0) is selected because of a typically significantly decreased model performance in predicting global vegetation productivity for anomalies compared to time series that include the mean seasonal cycles 5 , 70 , while it can still be efficiently used to study relationships between predictor variables and targets. Regions with R 2 < 0 are mostly associated with very low LAI variability or frequent human management (Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…We remove grid cells that have model performance worse than the mean of training data itself using cross-validation out-of-bag score (OOB R 2 > 0). We note that the rather low threshold (OOB R 2 > 0) is selected because of a typically significantly decreased model performance in predicting global vegetation productivity for anomalies compared to time series that include the mean seasonal cycles 5 , 70 , while it can still be efficiently used to study relationships between predictor variables and targets. Regions with R 2 < 0 are mostly associated with very low LAI variability or frequent human management (Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, substantial attention has been paid to large-scale and global-scale hydrological modeling [252][253][254]. Although only experimental catchments have sufficient data to perform a reliable hydrological prediction, the global availability of climatological, hydrological, and remote sensing data allows for the parametrizing of the global-level hydrological model.…”
Section: From Small-scale To Global-scale Hydrological Modelingmentioning
confidence: 99%
“…Owing to the use of observational data, SINDBAD shows a similar or better performance in simulating TWS seasonality and IAV compared to an ensemble of global hydrological and land surface models (Trautmann et al, 2018). H2M has also been applied for different climatic regions over the globe to simulate TWS seasonality and interannual variability, where it is shown that H2M is capable to learn key patterns of the global water cycle components and has a comparable performance and better local adaptivity, compared to four state-of-the-art global hydrological models (Kraft et al, 2022). In summary, the two model simulations used here provide state-of-the-art where the model parameters and processes are partly learnt from GRACE observations, and are comparable to state-of-the-art hydrological models commonly used.…”
Section: Global Hydrological Model Simulationsmentioning
confidence: 99%
“…. Studies have reported that global hydrological models performed relatively worse in reproducing observed global TWS interannual variability (IAV) compared to other temporal scales (e.g., Zhang et al, 2017;Kraft et al, 2022). Jensen et al (2020) showed that the longer term variability of TWS is dominant in GRACE compared to seasonal variations in Earth system models; and suggested that the models are less reliable in reproducing the timing of peaks of TWS IAV across years compared to the magnitude and frequency.…”
mentioning
confidence: 99%